Team Process Measurement: A Comparison of Criterion-Related Validity of Teamwork Appraisal Tools - Islam , Sayeedul; Nieman-Gonder , Jennifer; Cassel , David (American Journal of Management, 2021)
As organizations compete in an increasingly VUCA environment, performance appraisal processes become more important to their success. This is especially true as teams are implemented in organizations as a tool to make complex decisions. Little work has been done to assess the effectiveness of performance appraisal tools in predicting objective team performance. In the present study, 57 students organized into 19 3-person teams to work on a task. Results indicate that team process measurements were strongly correlated with one another but were not very predictive of objective team performance. Teams that viewed themselves as “real” teams were correlated with task performance. Future research should evaluate other team process measures for their criterion-related validity.